2016
DOI: 10.1073/pnas.1608130113
|View full text |Cite
|
Sign up to set email alerts
|

Cook Island artifact geochemistry demonstrates spatial and temporal extent of pre-European interarchipelago voyaging in East Polynesia

Abstract: The Cook Islands are considered the “gateway” for human colonization of East Polynesia, the final chapter of Oceanic settlement and the last major region occupied on Earth. Indeed, East Polynesia witnessed the culmination of the greatest maritime migration in human history. Perennial debates have critiqued whether Oceanic settlement was purposeful or accidental, the timing and pathways of colonization, and the nature and extent of postcolonization voyaging—essential for small founding groups securing a lifelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…Some have suggested that the Cook Islands were a gateway for colonisation of East Polynesia (Allen & Wallace ), and recent research provides evidence for prehistoric movement of lithic materials between the Cooks and other islands of West and East Polynesia (Weisler et al . ). The connection of Pukapuka, and to a lesser extent Aitutaki, to the Hawaiian and Society Islands may offer further evidence of the Cook Islands’ regional role.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Some have suggested that the Cook Islands were a gateway for colonisation of East Polynesia (Allen & Wallace ), and recent research provides evidence for prehistoric movement of lithic materials between the Cooks and other islands of West and East Polynesia (Weisler et al . ). The connection of Pukapuka, and to a lesser extent Aitutaki, to the Hawaiian and Society Islands may offer further evidence of the Cook Islands’ regional role.…”
Section: Discussionmentioning
confidence: 97%
“…; Weisler et al . ). However, it is significant that many of the strongest relationships revealed here are between islands of different archipelagos (see Figures a & b).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The geographic separation between the islands of the Indo-Pacific region is useful archaeologically as it allows the teasing apart of processes related to migration from those related to trade and other forms of contact. This is more difficult in mainland Southeast Asia (Fitzpatrick and Anderson, 2008), although it is now recognised that even in the Pacific most islands are unlikely to have ever been completely socioculturally and biologically isolated (Broodbank, 2002;Weisler et al, 2016). Current research in the Pacific is now showing extensive trade links after initial colonisation including retention of contact with the Southeast Asian mainland (Clark, G.R.…”
Section: Migration and Mobilitymentioning
confidence: 99%